Analysis of Procake Cake Shop Business Development Strategy - Rahmatullah, Hanief Rizqi; Priatini, Woro; Kusuma, Mandradithya (Gastronomy Tourism Journal, 2019)
The changing time situation can increase business opportunities or threats for the company. One effort to find out the right strategy for the company is a SWOT analysis. There is an analysis of the internal environment, namely strengths and weaknesses, an analysis of the external environment, namely opportunities and threats. Thus, it is expected to be prepared in accordance with the predetermined business plan formulation. This research focuses on the question of how the company's position in the internal and external environment and what marketing strategies are applied to the Procake Shop based on SWOT analysis. The form of this research is a descriptive method with a quantitative approach. Data analysis techniques used in this study are using IFAS Matrix, EFAS Matrix, IE Matrix, SWOT Matrix and QSPM Matrix. IFAS and EFAS matrix analysis results are known that the internal factors with the highest score are product quality and prices, while for external factors is the bakery business trend. Based on the results of the IE matrix, Procake Cake Shop located in cell II is Growth. The position shows that the strategy used by the company is to expand the company by building in other locations, and improving the types of products and services. Based on the results of the Procake Cake SWOT quadrant position is in quadrant I, which supports an aggressive strategy that shows that the company has opportunities and strengths that can take advantage of existing opportunities. Therefore the authors recommend five alternative strategies for developing a Procake Cake Shop business based on an analysis of the SWOT matrix. Through QSPM data processing, it can be seen that alternative strategies are the main priority to be implemented at Procake Cake Shop is to expand the product sales network through consignment or joint ventures in winning the potential of the bakery business with a value of 6.11 Stas.